2022
DOI: 10.7759/cureus.28579
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Carcinoma, Cyclooxygenases, and COX Inhibitors

Abstract: Colorectal carcinoma (CRC) is the most common of gastrointestinal cancers, the majority presenting with sporadic occurrence compared to the less frequently inherited syndromes. The increasing incidence, decreasing gender and age disparities, and the prevalent risk factors are concerning. The malignancy arising from benign precursor polyps transforms slowly over time. The adenoma variant polyps reported a marked upregulation of cyclooxygenases (COX), significantly COX-2 isoform, influenced by various determinan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Differential COX-2 expression may affect the likelihood that gastrointestinal adenocarcinomas, such as CRC, may develop (9) . Since specialised COX-2 inhibitors, such as different non-steroidal anti-inflammatory medications (NSAIDs), COX-2 is of special relevance since it has been created or is being produced and may have a role in the chemoprevention of gastrointestinal neoplasms (10) .…”
Section: Introductionmentioning
confidence: 99%
“…Differential COX-2 expression may affect the likelihood that gastrointestinal adenocarcinomas, such as CRC, may develop (9) . Since specialised COX-2 inhibitors, such as different non-steroidal anti-inflammatory medications (NSAIDs), COX-2 is of special relevance since it has been created or is being produced and may have a role in the chemoprevention of gastrointestinal neoplasms (10) .…”
Section: Introductionmentioning
confidence: 99%
“…The ability of celecoxib to inhibit the COX-2 enzyme with subsequent decreased PGE2, which plays a crucial role in the generation of VEGF, may be the cause of the suppression of angiogenesis translated by decreased VEGF levels by the concurrent use of celecoxib with FOLFIRI [ 23 ]. When compared to sporadic forms, COX inhibition has shown statistically significant results in lowering the risk of familial CRC [ 4 ].…”
Section: Reviewmentioning
confidence: 99%
“…About five percent of new-onset CRC cases have a genetic component associated with carcinogenesis [ 2 , 3 ]. It affects men more than women and is more common in developed countries, such as the USA, due to lifestyle changes, including a lack of exercise and dietary habits predominantly involving meat and alcohol [ 4 ]. Fruits and dietary fiber are important components of a healthy diet and have been associated with various health benefits, including potential protective effects against CRC [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…For decades, epidemiological studies have shown Sulindac, Aspirin, and Celecoxib to have a preventive action against CRC [7,8]. Sulindac and Celecoxib are beneficial in preventing the development of colorectal cancer in persons with the Adenomatous Polyposis Coli (APC) gene mutation [9]. Patients with the APC gene mutation present with adenomas in the colon, which progress into colon cancer if resection is not done [10].…”
Section: Introductionmentioning
confidence: 99%
“…Tumor cells can also produce excess PGE2, which acts in a paracrine/autocrine mechanism to promote angiogenesis through increased production of VEGF [14]. However, some reports have indicated that the effects of the drugs on CRC are more dependent on COX-independent pathways than COX-dependent pathways [9]. The claim is supported by a report that high levels of prostaglandin in-vitro and in-vivo inhibit cancer growth.…”
Section: Introductionmentioning
confidence: 99%